Gestión financiera en la cooperativa de ahorro y Crédito San Antonio Ltda. Los Ríos, agencia Babahoyo en el periodo 2023. - Zamora Gordillo, Luisa Fernanda (2025)
This case study deals with Financial Management in the San Antonio Savings and Credit Cooperative LTDA. Los Ríos, Babahoyo Agency in the period 2023, knowing that it constitutes a fundamental pillar that is directly related to the institution's ability to meet institutional objectives and goals, for which the objective is to analyze financial management in the San Antonio Savings and Credit Cooperative Ltda., Babahoyo agency, by evaluating the financial statements during the period 2023. In the present case study, the Financial, Administrative, Tax, Audit, Control Management research line and the Audit and Control research subline were used. On the other hand, in the present investigation, the mixed methodology was used, which integrates the qualitative and quantitative approaches, deductive reasoning and the descriptive type of research were also used, and the interview was selected as the information collection technique. Finally, the development of this work allowed us to draw relevant conclusions and recommendations on Financial Management in the San Antonio Savings and Credit Cooperative LTDA. Los Ríos, Babahoyo Agency.